STUDI PENDAHULUAN KATALIS BIAYA RENDAH UNTUK PRODUKSI METANOL DENGAN TARGET SEBAGAI PROSES KELANJUTAN DARI MODEL SISTEM GASIFIKASI PADA FLUIDIZED BED BERKATALIS - Joni .; Adiarso .; Galuh .; Nurdiah .; Tyas .; Bralin .; Erlan . (Jurnal Ilmiah Teknik Kimia, 2017)
Utilization of coal as well as its processing as an alternative energy is quite large in Indonesia and absolutely necessary. Especially on coal with low calorific value such as lignite, handling with direct combustion as in conventional coal power plant is an environmentally friendly manner because its emission contains harmful substances NOx and CO. With clean coal technologies (such as gasification), emissions of harmful substances into the environment can be reduced. This gasification process, coal is converted into syngas which is an intermediate product that can be directed into various types of alternative fuels such as methanol.Development of efficient and low cost methanol synthesis from syngas produced from gasification of coal has been our interest, in particular development  of low cost catalyst which is shown by Low Pressure Fixed Bed Reactor. In this research scheme, we develop the catalyst using Co-precipitation method and Copper based catalyst.. In this preliminary study, the synthesis of catalysts based on CuZnAl has been performed and tested in once trough process micromeritic reactor at mild operating condition. The results show that methanol synthesis at 20 bar and 270oC reach a good conversion, i.e. 1.15% of methanol at Molar Ratio (Cu:Zn / CuZn: Al2O3): 4: 3: 1. These results have been compared to commercial catalysts on the same conditions which reached 0.26% of methanol .  Kata Kunci : low rank coal, methanol synthesis, low cost catalyst, low pressure fixed bed reactor